Implementing the Learning-by-Play Method to Enhance Children's Motor Development and Creativity Students - Siti Afifatun; Junani Junani; Heri Cahyono; Andriyanto Andriyanto; Siti Atini (BASICA, 2025)
This study aims to analyze the application of the learning by playing method in improving the motor development and creativity of students at Daru Khoir Kindergarten, North Lampung. This study uses a qualitative field research method with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the principal, teachers, and students. The application of the learning by playing method is carried out through various educational activities such as movement games, drawing, coloring, building blocks, collages, and interactive group games. The results of the study show: first, the application of the learning by playing method is carried out through active, interactive, and fun play-based learning so that students are easier to follow the learning process and are directly involved in various motor and creative activities. Second, supporting factors for the development of motor and creativity of students include interesting learning methods, the active role of teachers, and the availability of educational learning media, while inhibiting factors include limited children's concentration, excessive use of gadgets, and limited certain learning facilities. Third, the application of the learning by playing method has positive implications for the development of gross and fine motor skills, increased creativity, self-confidence, social skills, and the creation of a more participatory and enjoyable learning atmosphere. Thus, the learning by playing method is an effective learning alternative in supporting the development of early childhood in the PIAUD environment.